THERMOSTABILITY IMPROVEMENT OF A RECENTLY DEVELOPED LIVE ATTENUATED SUDANESE CAMELPOX VACCINE (Journal of Veterinary Medicine and Animal Production, 2022)
A sudanese camel pox (CMP) candidate vaccine recently developed was subjected to gradual heating to improve its thermostability. Thermostability testing of the vaccine revealed that at 56˚C all the formulations lost their titer quickly with more than 3 to 5 log disappeared only in 30 and 60 minutes of incubation, respectively. The virus was then subjected to - heating at 56˚C for increasing time periods; the final passage was then retested for thermostability. Thermostability retesting of the recovered virions revealed that at 56˚C wild type virus and the attenuated candidate vaccines lost a titer of - and - log10 CCID50 upon incubation for 30 and 60 minutes, respectively.Compared with the original vaccine virus, a degree of thermostability improvement of the candidate vaccinewas attained. The information gathered in this work showed that; it is possible for the treated CP vaccine to have adequate short-term stability at non-freezing temperatures to support manufacturing, short-term shipping and storage. Improving thermostability should significantly enhance the utility of the vaccine during the field work for the control of CMP outbreaks.
Keywords: camelpox; thermostability; vaccine